Perlindungan Hukum Bagi Guru Terhadap Tindak Pidana Penganiayaan Yang Dilakukan Siswa - Soli Deo Glory O.Wagiu; Jocefina B. Tendean; R. Rigen Sumilat; Johanis L.S.S. Polii; Rinny Ante (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
The teacher is an important component in the teaching and learning process. A teacher participates in efforts to form potential human resources in the field of development, and a teacher is a person who has authority and responsibility to guide and develop students. Teachers must also avoid punishing students by hitting or carrying out actions that could hurt students. This view of discipline is apparently not well accepted by students, which makes the relationship between students and teachers relatively worse along with the decline in the culture of politeness and the lack of success in character in the world of education. Understanding that bad character can influence students behavior and make them more likely to fight back or commit disgraceful actions that cross the line, this happens based on students who feel unhappy when receiving a reprimand whether it’s because the are embarrassed, feel unfair, or feel less appreciated and understandable. That is the reason why students are starting to carry out acts of resistance, ranging from ordinary protest to the most serious cases such as criminalization or criminal acts of abuse. So the research problem can be formulated as follows: 1. What are the legal regulations for teachers regarding criminal acts of abuse committed by students? 2. What are the legal protection measures for teachers against criminal acts of abuse committed by students. In writing this thesis, the author used qualitative methods with a normative juridical approach. Regulations regarding legal protection for teachers are often not in line with child protections law, making laws for teachers tend to be weakened. However, all government efforts are also supported by PGRI, the police and the courts so the protection for teachers from acts of students abuse can be carried out according to applicable procedures.